Determination of the heat transfer coefficient of a rotary film evaporator with a heating filmforming element - Zahorulko, Andrii; Zagorulko, Aleksey; Cherevko, Oleksander; Dromenko, Olena; Solomon, Alla; Yakobchuk, Roman; Bondarenko, Oksana; Nozdrina, Nataliia (My University, 2021)
A model of a rotary film evaporator with a film-forming element with a reflective heated surface has been developed. This will allow stabilizing the hydraulic movement of the cut wave flow due to the reflective surface of the geometric shape for the forced direction of the cut raw material to the heating surface. Autonomous heating of the reflective surface additionally provides a temperature effect in the conditions of movement of particles of raw materials after cutting. The analysis of the experimental and theoretical parameters of heat transfer made it possible to substantiate the criterion equation for determining the heat transfer coefficient of an evaporator with the proposed film-forming element and a reflective heated surface for calculating the coefficient from the working surface to the raw material. The resulting equation takes into account the influence of the vertical component of the motion of the raw material film, centrifugal movement during the rotation of the film-forming element, mixing of the boiling film of the raw material with steam bubbles, and the geometric characteristics of the film-forming blade on the hydrodynamic flow of the raw material. The calculation of the rotary-film evaporator was carried out using the criterion equation and the obtained useful heat exchange surface – 0.75 m2. The specific metal consumption in a rotary film evaporator with a film-forming element having a reflective surface is 57 kg/m2, compared to the vacuum evaporator traditionally used in canning industries (410 kg/m2), which is 7.1 times less. The duration of the temperature effect on the raw material is also reduced: a rotary film evaporator – 200 s and 3600 s in a traditional apparatus. The data obtained will be useful for the design of rotary-film devices of different geometric parameters using articulated blades with a reflective plate.
Keywords: heat transfer coefficient; rotary film evaporator; criterion equation; film-forming element; organic raw; materials; кафедра технологічного обладнання та комп’ютерних технологій проектування